A new method for prediction 3G path loss propagation in suburban of Thailand - Bhupuok, Wiyada; Dejhan, Kobchai (My University, 2012)
This paper proposes the prediction propagation of path loss band 2100 MHz 3G, the mobile in suburban of Thailand. The selected site is Pathum Thani province which has a few of construction. This experiment measured the signal at different distance and different direction from mobile base stations. The results from experiment will be compared with the calculating value in order to make the new empirical model that will be suitable in suburban of Thailand. The statistical method Root Mean Square Error (RMSE) and Okumura model are used in this paper. © 2012 IEEE.
Keywords: okumura model; path loss; root mean square error (RMSE)